Debt and growth: Historical evidence - Christian Breuer; Carsten Colombier (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2020)
In this paper we examine the relationship between public debt and economic growth in a large historical panel dataset of 17 OECD economics over the period 1870 - 2016. We do not provide evidence for a statistically significant and robust relationship between government debt and growth. While our baseline regressions support the "conventional view" that government debt is negatively associated with economic growth, particularly in the aftermath of World War II, these results appear to be not robust to alternative specifications.
Keywords: E62; H56; H63; 330; Government Debt; Economic Growth; Robustness